Memory and Oblivion in the Ancient World: Interview with Prof. Dr. Fábio Vergara Cerqueira - Maria Aparecida de Oliveira Silva; Fábio Vergara Cerqueira (Revista do Museu de Arqueologia e Etnologia)
The interview with Professor Fábio Vergara Cerqueira addresses themes of memory, forgetting, heritage, and tradition, which have gained prominence in humanities debates. He explores the concept of the "age of mnemotropism," where memory takes center stage in social issues. The professor discusses the disputes surrounding memory and forgetting, highlighting two types: "natural" forgetting, resulting from the wear of materials or urban renewal, and "political" forgetting, such as damnatio memoriae, where deliberate erasure and intentional invisibility occur. Identity and sense of belonging issues also stand out, as they are intertwined with matters related to memory and forgetting.